Rapid Lava Sand Filtration for Decentralized Produced Water Treatment System in Old Oil Well Wonocolo - Ekha Yogafanny; Ayu Utami; Kristiati E. A.; Wibiana W. Nandari (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
The Cepu Block Oil Field has been traditionally extracted since 2008 by the local community in Wonocolo. The oil well-produced gas and fluids consisted of crude oil and produced water. This oil production activity discharges high amounts of produced water. The fluids have been settled down in the sedimentation tank to gain the crude oil optimally. The remaining fluid called produced water has been discharged to the surface towards the river without any further treatment. This activity led to the deterioration of environmental quality. This study aimed to analyze the performance of produced water treatment by rapid sand filtration by measuring the degree of turbidity removal under the specific condition on a laboratory scale using lava sand. The sedimentation was conducted in 3 hours of retention time following the real field condition of the oil production process by community in one sample well. The rapid sand filtration was conducted by a fixed bed column method with 0.2 cm of grain size. The sedimentation process followed by the rapid sand filtration in produced water treatment yielded the high efficiency of turbidity removal reaching 98.65 %. The rapid sand filter also worked excellently in turbidity removal attaining 96.48 % of efficiency. These results confirmed that the sedimentation already done by the community followed by the rapid sand filtration is promising decentralized technology to be applied in a remote area such as Old Oil Wells Wonocolo regarding turbidity removal.